Memory of the vernalized state in plants including the model grass Brachypodium distachyon - Woods, Daniel P.; Ream, Thomas S.; Amasino, Richard M. (Frontiers in Plant Science, 2014)
Plant species that have a vernalization requirement exhibit variation in the ability to “remember” winter—i.e., variation in the stability of the vernalized state. Studies in Arabidopsis have demonstrated that molecular memory involves changes in the chromatin state and expression of the flowering repressor FLOWERING LOCUS C, and have revealed that single-gene differences can have large effects on the stability of the vernalized state. In the perennial Arabidopsis relative Arabis alpina, the lack of memory of winter is critical for its perennial life history. Our studies of flowering behavior in the model grass Brachypodium distachyon reveal extensive variation in the vernalization requirement, and studies of a particular Brachypodium accession that has a qualitative requirement for both cold exposure and inductive daylength reveals that Brachypodium can exhibit a highly stable vernalized state.